2023
DOI: 10.1002/anie.202312255
|View full text |Cite
|
Sign up to set email alerts
|

Adapting Synthetic Models of Heme/Cu Sites to Energy‐Efficient Electrocatalytic Oxygen Reduction Reaction

Jia Meng,
Haonan Qin,
Haitao Lei
et al.

Abstract: In nature, cytochrome c oxidases catalyze the 4e− oxygen reduction reaction (ORR) at the heme/Cu site, in which CuI is used to assist O2 activation. Because of the thermodynamic barrier to generate CuI, synthetic Fe‐porphyrin/Cu complexes usually show moderate electrocatalytic ORR activity. We herein report on a Co‐corrole/Co complex 1‐Co for energy‐efficient electrocatalytic ORR. By hanging a CoII ion over Co corrole, 1‐Co realizes electrocatalytic 4e− ORR with a half‐wave potential of 0.89 V versus RHE, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 55 publications
0
1
0
Order By: Relevance
“…The mechanisms of biologically essential metalloenzymes such as amine oxidases, including peptidyl glycine-α-hydroxylating monooxygenase (PHM) and dopamine-β monooxygenase (DβM), rely heavily on copper–oxygen reactive intermediates such as copper( ii )-superoxo species formed from the binding and activation of dioxygen by a single copper-ion site. 1–12 Previous mechanistic studies have revealed that the substrate hydroxylation reaction mechanisms of PHM and DβM are quite similar. 13,14 Apart from these two enzymes, galactose oxidase and lytic polysaccharide monooxygenase are two other enzymes where cupric-superoxide is found to play a critical role in their functioning.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanisms of biologically essential metalloenzymes such as amine oxidases, including peptidyl glycine-α-hydroxylating monooxygenase (PHM) and dopamine-β monooxygenase (DβM), rely heavily on copper–oxygen reactive intermediates such as copper( ii )-superoxo species formed from the binding and activation of dioxygen by a single copper-ion site. 1–12 Previous mechanistic studies have revealed that the substrate hydroxylation reaction mechanisms of PHM and DβM are quite similar. 13,14 Apart from these two enzymes, galactose oxidase and lytic polysaccharide monooxygenase are two other enzymes where cupric-superoxide is found to play a critical role in their functioning.…”
Section: Introductionmentioning
confidence: 99%
“…Metalloenzymes, such as cytochrome c oxidase and cytochrome P450, demonstrate that first row transition metals can indeed efficiently activate O 2 . Heme enzymes, in particular, have inspired a variety of homogeneous and heterogeneous electrocatalysts for ORR consisting of first-row transition metals and either porphyrin, corrole, or phthalocyanine ligands. Although most of these electrocatalysts are highly selective for the four electron reduction of O 2 to H 2 O, they require effective overpotentials that are likely too high for practical use . Cobalt complexes with porphyrin, corrole, and phthalocyanine ligands tend to have lower overpotentials but slower activity and lesser selectivity for H 2 O than their iron-containing analogs. …”
Section: Introductionmentioning
confidence: 99%
“…19–21 The unique structures of corroles not only make them possess attractive coordination capabilities and specific reactivities but also make them ideal acceptors in D–A systems. 22–29 Not only that, functionalized corroles, such as 5,10,15-tris( p -aminophenyl)corrole (TPAPC), can be further used as acceptors to construct novel D–A systems. 20–23,30 Furthermore, corroles usually possess small HOMO–LUMO gaps that cause electrons to be easily adsorbed and released, permitting rapid electron transfer to reactants and enhancing electrocatalytic activities.…”
Section: Introductionmentioning
confidence: 99%